Treatment of multiple sclerosis with rituximab: A Spanish multicenter experience - Gascón-Giménez, Francisco; Alcalá, Carmen; Ramió-Torrentà, Lluís; Montero, Paloma; Matías-Guiu, Jorge; Gómez-Estevez, Irene; Oreja-Guevara, Celia; Gil-Perotín, Sara; Blanco, Yolanda; Carcelén, María; Quintanilla-Bordás, Carlos; Costa, Lucienne; et al. (Frontiers in Neurology, 2023)
Introduction Rituximab (RTX) is considered a potential therapeutic option for relapsing-remitting (RRMS) and progressive forms (PMS) of multiple sclerosis (MS). The main objective of this work was to investigate the effectiveness and safety of rituximab in MS. Patients and methods Observational multicenter study of clinical and radiological effectiveness and safety of rituximab in RRMS and PMS. Results A total of 479 rituximab-treated patients were included in 12 Spanish centers, 188 RRMS (39.3%) and 291 (60.7%) PMS. Despite standard treatment, the annualized relapse rate (ARR) the year before RTX was 0.63 (SD: 0.8) and 156 patients (41%) had at least one gadolinium-enhanced lesion (GEL) on baseline MRI. Mean EDSS had increased from 4.3 (SD: 1.9) to 4.8 (SD: 1.7) and almost half of the patients (41%) had worsened at least one point. After a median follow-up of 14.2 months (IQR: 6.5–27.2), ARR decreased by 85.7% (p < 0.001) and GEL by 82.9%, from 0.41 to 0.07 (p < 0.001). A significant decrease in EDSS to 4.7 (p = 0.046) was observed after 1 year of treatment and this variable remained stable during the second year of therapy. There was no evidence of disease activity in 68% of patients. Infusion-related symptoms were the most frequent side effect (19.6%) and most were mild. Relevant infections were reported only in 18 patients (including one case of probable progressive multifocal leukoencephalopathy). Conclusion Rituximab could be an effective and safe treatment in RRMS, including aggressive forms of the disease. Some selected PMS patients could also benefit from this treatment.